2014
DOI: 10.1161/hypertensionaha.114.03957
|View full text |Cite
|
Sign up to set email alerts
|

Age-Specific Differences Between Conventional and Ambulatory Daytime Blood Pressure Values

Abstract: E levated blood pressure (BP) is one of the strongest risk factors for morbidity and mortality worldwide. 1 BP-lowering treatment has been shown to be highly effective in preventing hypertension-related cardiovascular events. 2 Accordingly, an accurate diagnosis of hypertension is crucial to target treatment to those individuals at high risk for adverse events. Abstract-Mean

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
55
4
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 26 publications
7
55
4
2
Order By: Relevance
“…At variance with prior studies, [14][15][16]27 we did not find significant changes in the direction of the mean BP differences between clinic and ambulatory BP values at any particular age, even in untreated patients. In other words, these BP differences were generally positive, that is, higher clinic than daytime ABPM values across all age groups.…”
Section: Comparison With Other Studiescontrasting
confidence: 89%
See 2 more Smart Citations
“…At variance with prior studies, [14][15][16]27 we did not find significant changes in the direction of the mean BP differences between clinic and ambulatory BP values at any particular age, even in untreated patients. In other words, these BP differences were generally positive, that is, higher clinic than daytime ABPM values across all age groups.…”
Section: Comparison With Other Studiescontrasting
confidence: 89%
“…5,8 More recently, a meta-analysis of population studies on adults and children performed in 1990 to 2009 and a recent study from the IDACO (International Database on Ambulatory Blood Pressure and Cardiovascular Outcomes) on 13 population-based cohorts have described higher clinic than daytime BP only in older subjects, but higher daytime than clinic BP in subjects under the age of 50 years. 14,15 Similar results (daytime BP higher than clinic BP) have been described in children and adolescents. 16,17 Most of these previous studies were centered on untreated populations, 5,14,15 and most prior clinical studies have been small (<200 subjects).…”
Section: Hypertensionsupporting
confidence: 75%
See 1 more Smart Citation
“…Single-drug therapy reduced Relevant 2° endpoint: Active treatment also reduced the risk of total major vascular events (26% [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]). There were similar reductions in the risk of stroke in hypertensive and nonhypertensive subgroups (all p<0.01).…”
Section: Key Findingsmentioning
confidence: 99%
“…Conen and colleagues 18 recently demonstrated that the prevalence of WCHT exponentially increased from 2.2% to 19.5% from those aged 18 to 30 years to those aged ≥70 years. WCHT is also more prevalent among female gender.…”
mentioning
confidence: 99%